Do carrier expectations indicate industry structure in container shipping? An econometric analysis - Michael Fusillo; Hercules E. Haralambides (Journal of Shipping and Trade (JST), 2020)
In the competitive environment of liner shipping, the ability to nimbly adjust shipping capacity to demand could mean the difference between a thriving shipping operation and one that will most likely fail. How quickly and effectively carriers adjust their capacity may depend on how their expectations regarding trade volumes and freight rates are formed. We find that if adaptive expectations prevail in the decision process, capacity deployment may suffer some degree of inertia but, compared to expectations that are formed rationally, capacity would be be relatively stable. On the other hand, if carrier expectations are rational, capacity deployment might be more likely to align closer and faster with demand. We seek to empirically test whether carriers' expectations of demand, aiming at deploying the right amount of capacity, can be characterized as adaptive or rational. We find that a) in most cases, adaptive expectations is the paradigm in container shipping; b) the way expectations are formed and the market structure of the liner shipping industry are two things not totally unrelated; and c) rational expectations point to more competitive markets (such as that of the Pacific), while adaptive expectations indicate higher concentration and thus imperfect competition (as is the case in the North Atlantic). Our findings have important regulatory implications in the sense that, if one accepts, as we do, that adaptive expectations are consistent with concentrated industries, while rational expectations suggest more competition, then our paper suggests that the 2008 abolition of the liner conference system from European trades has failed to improve the level of competition in the Europe - US liner shipping markets.
Keywords: 650; Liner shipping; Container shipping; Liner conferences; Freight rate fluctuations; Rational expectations; Adaptive expectations; Regulation in shipping; Liner consortia block exemption; Market structure